FORMATION OF FLUORINE-RICH MAGMAS BY FLUID FILTRATION THROUGH SILICIC MAGMAS: PETROLOGICAL AND GEOCHEMICAL EVIDENCE OF METAMAGMATISM - Abramov S.S. (My University, 2004)
The formation of fluorine rich magmas by fluid filtration through silicic magmas was described. Retrograde magma boiling in a large magma chamber produced an increase in pressure which resulted either in explosive ejection of melt on the surface or in passive chamber degassing. It was found that if the oxygen fugacity in the magmatic source of fluids was higher than QFM+1...+2, fluid filtration led to the formation of high fluorine oxidized melts. The modeling of the dynamics of heat and mass transfer, which showed the development of an open magmatic system was also presented.
Keywords: fluorine rich magmas